Fatigue and Its Association With Quality of Life Among Carers of Patients Attending Psychiatric Emergency Services During the COVID-19 Pandemic - Ji, Xiao; Li, Wen; Zhu, Hui; Zhang, Ling; Cheung, Teris; Ng, Chee H.; Xiang, Yu-Tao (Frontiers in Psychiatry, 2021)
Aims: Carers of psychiatric patients often suffered from mental and physical burden during the COVID-19 pandemic due to the lack of mental health services. This study investigated the pattern of fatigue and its association with quality of life (QOL) among the carers of patients attending psychiatric emergency services during the COVID-19 pandemic. Methods: In this cross-sectional study, carers of patients attending psychiatric emergency services during the COVID-19 pandemic were consecutively included. Fatigue, insomnia symptoms, depressive symptoms, and QOL were assessed with standardized instruments. Results: A total of 496 participants were included. The prevalence of fatigue was 44.0% (95%CI=39.6%-48.4%). Multivariate logistic regression analysis revealed that fatigue was positively associated with higher education level (OR=1.92, P<0.01) and more severe depressive (OR=1.18, P<0.01) and insomnia symptoms (OR=1.11, P<0.01). ANCOVA analysis revealed that the QOL was significantly lower in carers with fatigue compared to those without (P=0.03). Conclusions: Fatigue was common among carers of patients attending psychiatric emergency services during the COVID-19 pandemic. Considering the adverse impact of fatigue on QOL and other health outcomes, routine screening and appropriate intervention for fatigue are warranted for this subpopulation.